Lamb production responses to grass grazing in a companion crop system with corn silage and oversowing of yellow oat in a tropical region - Pariz, Cristiano M. [UNESP]; Costa, Ciniro [UNESP]; Crusciol, Carlos A.C. [UNESP]; Castilhos, André M. [UNESP]; Meirelles, Paulo R.L. [UNESP]; Roça, Roberto O. [UNESP]; Pinheiro, Rafael S.B. [UNESP]; Kuwahara, Frank A.; Martello, Jorge M. [UNESP]; Cavasano, Francielli A. [UNESP]; Yasuoka, Júnior I.; Sarto, Jaqueline R.W. [UNESP]; et al. (Elsevier, 2017)
Integrated crop-livestock systems in regions with dry winters could be a viable option to increase food production during periods of irregular rain and reduced pasture availability. A corn (Zea mays L.) silage production system with cover crops of (a) the weedy growth of signal grass [Urochloa decumbens (Stapf) R. Webster “Basilisk”] and (b) palisade grass [Urochloa brizantha (Hochst. ex A. Rich.) R. Webster ‘Marandu’ and ‘Piatã’], both with a 0.20- and 0.45-m silage cutting height, was employed in the summer and autumn. Yellow oat (Avena byzantina cv. São Carlos) was oversown in these systems in the winter and spring. The pasture production, the daily ration intake, the performance and carcass characteristics of lambs (Ovis aries) grazing these pastures in a semi-feedlot system (supplemented with silage and concentrate), and the revenue were investigated. The experiment was repeated in the same location for two growing seasons (2010–2011 and 2011–2012) on a Typic Haplorthox in Botucatu, São Paulo, Brazil. Analyzing the system as a whole, intercropping corn silage with palisade grass cv. Marandu (followed by palisade grass cv. Piatã) with a cutting height of 0.45 m combined with yellow oat oversowing was the most robust option for enhancing productivity. The pasture formation for lamb finishing in a semi-feedlot system, the reduction of silage and concentrate intake, and greater live weight and carcass gains per hectare were key attributes for improving the economic viability of this integrated crop-livestock system. Thus, these crop systems were a viable option for the diversification of agricultural activities in tropical regions.
Keywords: Animal carcass; Avena byzantina; Integrated crop-livestock system; Live weight gain; Total operating cost; Urochloa brizantha